2018
DOI: 10.1111/papt.12201
|View full text |Cite
|
Sign up to set email alerts
|

Service users’ first accounts of experiencing endings from a psychological service or therapy: A systematic review and meta‐ethnographic synthesis

Abstract: Purpose. To review and synthesize the qualitative literature on service users' experiences of endings from a psychological service or therapy. Methods.A systematic search of the peer-reviewed literature identified qualitative studies meeting specific inclusion criteria. A modified CASP tool was used to critically appraise their quality, and a meta-ethnographic approach was used to synthesize their findings.Results. Twelve papers met the inclusion criteria. The interpretation of findings suggested three key the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The importance of a planned ending echoes findings from the general population literature. In their systematic review, Webb et al (2019) found that by experiencing a planned and well-prepared ending, clients felt more in control, which subsequently alleviated feelings of anxiety in relation to the impending end. Webb et al (2019) also reported that, as part of endings that go well, collaborative decisionmaking regarding the end of therapy alleviated associated feelings of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of a planned ending echoes findings from the general population literature. In their systematic review, Webb et al (2019) found that by experiencing a planned and well-prepared ending, clients felt more in control, which subsequently alleviated feelings of anxiety in relation to the impending end. Webb et al (2019) also reported that, as part of endings that go well, collaborative decisionmaking regarding the end of therapy alleviated associated feelings of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Webb et al (2019) found that by experiencing a planned and well-prepared ending, clients felt more in control, which subsequently alleviated feelings of anxiety in relation to the impending end. Webb et al (2019) also reported that, as part of endings that go well, collaborative decisionmaking regarding the end of therapy alleviated associated feelings of anxiety. Mangione et al (2007) found a similar result with therapists working in the general population: 36% of therapists surveyed suggested that endings should be jointly decided; however, in practice, this was less likely to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deductive coding framework was developed as a template to guide the deductive process (Crabtree and Miller, 1999). Codes were derived from the literature, namely, the National Institute of Health and Care Excellence (2009) guidelines and a systematic literature review on service users’ subjective experiences on endings (Webb et al , 2018). A refutational stage (step 4) was added as a process to ensure that the researchers considered contrasting data.…”
Section: Methodsmentioning
confidence: 99%
“…Within mental health-care services, endings are widely considered to be an important phase of therapy for both service users (Webb et al , 2008) and therapists (Råbu et al , 2013) across a wide range of clinical areas and therapy modalities and often elicit a complex emotive response (Wachtel, 2002).…”
Section: Introductionmentioning
confidence: 99%